2022
DOI: 10.3390/molecules27113438
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Properties by Ion Changing Based on Luminescent Ionic Salts Consisting of Spirobi(boron ketoiminate)

Abstract: We report development of luminescent ionic salts consisting of the boron ketoiminate structure, which is one of the robust skeletons for expressing aggregation-induced emission (AIE) properties. From the formation of the boron-centered spiro structure with the ketoiminate ligands, we obtained stable ionic salts with variable anions. Since the ionic salts show Tms below 100 °C, it was shown that these salts can be classified as an ionic liquid. By using PF6 anion, the single crystal—which is applicable for X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Similarly to common AIE-active molecules, these motions were effectively suppressed in the aggregation. As a result, solid-state luminescence was observed from the series of boron complexes and polymers. More recently, by introducing the fused structure at these AIE-active complexes for suppressing molecular motions, it was confirmed that the resulting fused boron complexes (FBKIs, Figure ) showed not only similar luminescence efficiencies in solution, solid, and amorphous but also mechanochromic luminescent behaviors. In particular, it was demonstrated that FBKIs are a platform for fabricating luminescent polymer films . The resulting polymers showed yellow emission, and red-shifts were observed in the films.…”
Section: Introductionmentioning
confidence: 95%
“…Similarly to common AIE-active molecules, these motions were effectively suppressed in the aggregation. As a result, solid-state luminescence was observed from the series of boron complexes and polymers. More recently, by introducing the fused structure at these AIE-active complexes for suppressing molecular motions, it was confirmed that the resulting fused boron complexes (FBKIs, Figure ) showed not only similar luminescence efficiencies in solution, solid, and amorphous but also mechanochromic luminescent behaviors. In particular, it was demonstrated that FBKIs are a platform for fabricating luminescent polymer films . The resulting polymers showed yellow emission, and red-shifts were observed in the films.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, the roles of counter ions in photoluminescent properties are not systematically examined. Although several cation‐based emitters were reported, [ 38–44 ] there are limited reports on anion‐based emitters. [ 45,46 ] Tohnai et.al .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the roles of counter ions in photoluminescent properties are not systematically examined. Although several cation-based emitters were reported, [38][39][40][41][42][43][44] there are limited [17][18][19] and b) nido-carborate anion (PYnCA). The red hydrogen atom is μ-H. reports on anion-based emitters.…”
Section: Introductionmentioning
confidence: 99%
“…Various element-blocks with mechanochromic luminescent properties have been reported, and it is suggested that intermolecular interaction could be the major factor for modulating luminescent color in solid. 17,18 Actually, since molecular distribution and subsequently degree of intermolecular interaction would be considerably different between crystal and amorphous, mechanochromic luminescent behaviors appear when regular structures in the solid-state luminescent crystalline materials are collapsed by mechanical forces. On the other hand, in order to avoid ACQ usually caused by intermolecular interaction in the condensed state, the introduction of bulky substituents is one of conventional strategies.…”
Section: Introductionmentioning
confidence: 99%